THE ACTUALIZATION OF ECONOMIC FIQH IN EMPOWERING THE SMALL TRADERS TO CHALLENGE ASEAN ECONOMIC COMMUNITY - Khasanah, Umrotul (Jurisdictie: Jurnal Hukum dan Syariah, 2021)
The small traders in traditional markets have become a unique phenomenon. In actualizing the Fiqh of Economy, they should be empowered. However, in socio-economic facts, small traders often face difficulties in obtaining fund assistance from formal financial institutions. This qualitative study reveals the role of the Economic Fiqh actualization in empowering small traders in the era of ASEAN Economic Community (AEC). They still face the classic problem i.e. limited access to capital. The credit distribution from conventional financial institutions should have been accessible for small traders to increase capital. However, in fact, it is not that easy due to lack of collateral and less elastic administrative management. Interestingly, amid the unfortunate situation, Sharia Microfinance Institutions (SMI) provide capital access for small traders. SMI transforms the existing system by providing easy access without collateral and elastic administration. Since 2015, Indonesia has entered the AEC committed to realizing economic equality in the ASEAN region by prioritizing the Micro, Small and Medium Enterprises (MSMEs) sector. With easy access to capital, it will encourage peopleâ€™s welfare and increase the economic growth of the community.Keberadaan pedagang kecil di dalam pasar tradisional menjadi fenomena unik. Secara aktualisasi fiqih ekonomi pedagang kecil mestinya harus diberdayakan. Namun, dalam fakta sosial-ekonomi, pedagang kecil kerap kali kesulitan mendapatkan bantuan modal dari lembaga keuangan formal. Penelitian kualitatif ini, mengungkapkan peran aktualisasi fiqih ekonomi dalam pemberdayaan ekonomi pedagang kecil di era Masyarakat Ekonomi ASEAN (MEA). Pedagang kecil masih menghadapi masalah klasik yaitu keterbatasan akses permodalan. Penyaluran kredit dari lembaga keuanganÂ konvensional, yang mestinya dapat diakses pedagang kecil untuk menambah modal, namun tak bisa diakses karena ketiadaan agunan dan pengelolaan administrasi yang kurang elastis. Menariknya, di tengah persoalan yang menghimpit para pedagang kecil, Lembaga Keuangan Mikro Syariah (LKMS) memberi akses pedagang kecil untuk mendapatkan modal. LKMS mentransformasi sistem yang ada, yaitu dengan memberikan kemudahan akses tanpa jaminan dan administrasi yang elastis. Sejak 2015, Indonesia telah memasuki MEA yang berkomitmen untuk mewujudkan pemerataan ekonomi di kawasan regional ASEAN dengan mengutamakan sektor Usaha Mikro Kecil Menengah (UMKM). Dengan akses permodalan yang mudah akan mendorong kesejahteraan masyarakat dan meningkatkan pertumbuhan ekonomi masyarakat.